SEAT AND VENUE AN ENDLESS CONTROVERSY - Rana, Sahil; Kaur, Inderpreet (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Alternative dispute resolution (ADR) mechanism gives deductively created procedures to Indian legal executive which helps in decreasing the weight on the courts. ADR offers to determine all kind of issues including common, business and so on, where individuals are not having the option to begin any kind of discussion and arrive at the settlement. One of the significant part in adr is arbitration both the national and international. In domestic arbitration the both the parties are only from India and Indian law is applied according to part I of the 1996act whereas in international commercial (ICA) refers to arbitration emerging out of questions between parties that are occupants or bodies consolidated in a country other than India. In such cases, the likelihood of disputes increments when parties are of various nations, making the seat versus venue question a subject of conversation. At the point when parties select the seat, it adopts the laws and regulation of the seated seat over the arbitration process.